Evaluation of brewers yeast as a feed supplement for common carp fingerlings (Cyprinus carpio) - Samad Sofy Omar (Polytechnic)
Feeding trial were carried out at the Aquaculture unit, Grdarasha station, Agriculture College, University of Salahaddin, Erbil, Kurdistan Region, to investigate different levels of Aquagrow E (AGEY) brewers yeast cell Saccharomyces cerevisiae on the growth and body composition of common carp juveniles Cyprinus carpio. The basal diet was formulated to contain 34% protein and 10% lipid and the dietary treatments were supplemented with 0.5%, 1% and 1.5% of AGEY diet. A total of 180 Common carp (10 g) fed on experimental diets for 70 days. Results of this study conducted that the growth performance and feed efficacy increased with increasing dietary AGEY supplementation. The final weight, weight gain, DGR, FCR and FCE were significantly improved in fish fed diets supplemented with 1.5% of AGEY. The highest SGR were significantly obtained in fish fed with 1.5% followed by those fed with 1% AGEY which was significantly higher compared to those fed with 0.5%and control diet. Also, PER was significantly improved in fish fed with 1-1.5% dietary treatments than those fed with control diet. Body protein was enhanced with the raising supplemented levels of AGEY in the dietary treatment and significant differences was observed only at 1.5% AGEY. Body lipids were fluctuated between dietary treatments, except in fish fed 1.5% of AGEY level which was significantly reduced. The results confirmed that AGEY at 1-1.5% enhanced growth performance and body composition of common carp juveniles.